Supply, installation and testing commissioning of exterior plumbing work from two number deep tube well already installed within the campus boundary and one line from the Wasa main line outside the main gate for the Brac University new campus building at holding no. Kha 224 Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and Endeavour Technologies Ltd. - Fast Technology and Ideas Corporation JV to supply, installation and testing commissioning of exterior plumbing work from two number deep tube well already installed within the campus boundary and one line from the Wasa main line outside the main gate for Brac University new campus project.